PERAN LEMBAGA KURSUS ANEKA SOUVENIR DALAM MENINGKATKAN EKONOMI WARGA BELAJAR DI PKBM INSAN MULIA KABUPATEN JOMBANG - Nanda Pratiwi Ismugawati; Rivo Nugroho; Maria Veronika Reosminingsih (JPUS: Jurnal Pendidikan Untuk Semua, 2020)
The main problem of this research is how the role of various souvenir course institutions in improving the economy of learning citizens in PKBM Insan Mulia, Jombang Regency. How all data is presented is original based on what is obtained from this research in the field. This study focuses on knowing the implementation of the course and the impact of following various souvenir courses in improving the economy of learning citizens.The main objective of this research is to be able to know how the role of various souvenir course institutions and how the role of course institutions in improving the economy of learning citizens when attending various souvenir courses. This research uses a qualitative research approach. Data collection techniques used were participant observation, interviews, and documentation.The results of the study indicate that the role of various souvenir course institutions in improving the economy of learning citizens is very influential for the sustainability of the course. PKBM Insan Mulia is able to become an independent non-formal educational institution and has a good management, where various souvenir courses can be attended by people who intend to take courses to gain knowledge, skills and capital to open business opportunities that can ultimately improve their economy.